Theoretical Study of Lithium Oxide Clusters Adsorbed on Anatase tio2 Surface - Cardenas-Jiron, G; Pino-Lopez, E; Pino-Rios, R; Zambrano-Angulo, M (Elsevier B.V., 2023)
The search for materials that have broad applicability as photocatalysts is growing interest. Titanium dioxide (TiO2) is a semiconductor with demonstrated photocatalytic properties, and its improvement with lithium oxide (LO) adsorption (LO-TiO2) is investigated using density functional theory (DFT). The modeling of the electronic structure of three types of LO as lithium oxide (Li2O)n, lithium peroxide (Li2O2)n, and lithium superoxide radical (LiO2)n (n = 1,2,3) adsorbed on anatase TiO2 shows an increase in their reactivities. The bandgap energy decreases in the range of 3.07–0.33 eV compared to TiO2 (3.2 eV) and conducting states from LO and 2p orbital of O(TiO2) towards 3d orbital of titanium (TiO2) are generated. The Independent Gradient Model and the intrinsic bond strength index are applied to gain insight into the intermolecular interactions between LO and TiO2. These results are coherent with that predicted by the interaction energy of LO-TiO2, which suggests that the more stable systems are (Li2O)2 and (Li2O2)3. Optical properties calculated with TD-DFT show a visible shift of the main absorption band compared to TiO2. The theoretical results show that the adsorption of lithium oxide onto a TiO2 surface would be an excellent strategy to produce a material as a visible light-activated photocatalyst. © 2023 Elsevier B.V.